PENGARUH MOTIVASI KERJA KARYAWAN TERHADAP KINERJA KARYAWAN PT ANINDYA MITRA INTERNASIONAL YOGYAKARTA - Sri Purwati; Ani Muttaqiyathun (Universitas Ahmad Dahlan, 2011)
This study aims to analyze the influence of work motivation on employee performance PT. Anindya International Partners in Yogyakarta. Research variables include: employee performance variable (Y) as the dependent variable and the variable need for achievement (X1), the variable need for power (X2), the variable need for affiliation (X3) as independent variables.This study used multiple linear regression analysis. The population in this study involves the employees of PT. Anindya International Partners in Yogyakarta. Samples are selected using the method of saturated samples, based on the population that has been described above, then the sample was selected in this study are 62 employees. Data collection techniques using questionnaires and literature study.Based on test results from t-test (linear regression test) partially on the need for achievement variable (X1) of 3.610> t-table = 2.000 and therefore contributes to employee performance variable (Y). In the variable need for power (X2) for 4.489 <t-table = 2.000, which means no effect on employee performance (Y). In the variable need for affiliation (X3) 1.961> t-table = 2.000 means no effect on employee performance (Y). While the F test (simultaneous test) to prove that the variable need for achievement (X1), the variable need for power (X2), the variable need for affiliation (X3), significantly affect employee performance (Y) equal to 39.137%.